Knowledge and behavioural factors associated with gender gap in acquiring HIV among youth in Uganda - Shraboni Patra; Rakesh Kumar Singh (SAGE Publishing, 2015)
Background. The increasing prevalence of HIV in Uganda during the last decade (7.5% in 2004-05 to 8.3% in 2011 among women and 5.0% in 2004-05 to 6.1% among men in 2011 of 15 to 49 years) clearly shows that women are disproportionately affected by HIV epidemic. Hence, we assessed the prevalence of HIV and focused on differences in risky sexual behaviour and knowledge of HIV among Ugandan youth. Design and Methods. Uganda AIDS Indicator Survey 2011 data was used. The total samples of men and women (15 to 24 years), interviewed and tested for HIV, were 3450 and 4504 respectively. The analysis of risky sexual behaviour was based on 1941 men and 3127 women who had ever had sex and were tested for HIV. Pearson's Chi-square test and multivariate logistic regression analysis were used. Results. Findings showed that young women were almost two times more vulnerable than young men in acquiring HIV (OR=1.762, P<0.001). Women who had first sex under age 15 (7.3%), had more than 2 sexual partners (9.2%) and did not use condom during last sex (6.4%) were more HIV-positive. Higher risk was found among women (6.3%) than men (2.2%). Significantly (P<0.01) less percentage (81.3%) of women as compared to men (83.8%) perceived that the probability of HIV transmission may be reduced by correct and consistent use of the condom during sex. Conclusions. Hence, there is an urgent need for effective strategies and programmes to raise awareness on sexual health and risky behaviour, particularly targeting the youth, which will reduce the gender gap in risky sexual behaviour and new transmission of HIV in Uganda.